Methode zur Bestimmung der Waldhöhengrenze - Svensson, Harald (ERDKUNDE, 1955)
The proposed method is an entirely cartographic one and requires the availability of contour maps. The sequence of operations is as follows: A hypsographic curve of the appropriate area is constructed, the upper limit of forest is marked on the map and the magnitude of the forest-free area above is measured. The altitude of the corresponding average upper limit of forest is then obtained from the hypsographic curve by marking on it the surface thus found. By using this method the effects of local climatic conditions such as exposure to wind and aspect as regards insolation are counter-balanced. This method was tested by calculating the upper limit of the birch forest in a strip of country straight across the Scandes. The area in question was divided into 26 squares, 13 to the north and 13 to the south of a base line. In each of these squares the upper limit of forest was then calculated by this hypsographic method (cf. table). The result is shown in diagram 2, in which the unbroken line represents the altitude of the forest limit in this transversal profile as found by this method, whereas the broken line indicates the upper limit of the birch forest as determined by Hansen2 from a number of places on the map. It might be pointed out that because of its basic principle, the method described is equally suitable for deter mining the lower limit of forest where such exists.